Effects of the number of people, temperature, relative humidity, and CO2 parameters on indoor air quality in higher education institution classrooms - Ateş, Ergun; Khameneh, Elham Talebi (Edelweiss Applied Science and Technology, 2023)
This study involved the measurement of air temperature, relative humidity, and CO2 levels in both open and closed circumstances of windows and doors, both indoors and outdoors, during educational activities in a higher education institution classroom. Air temperature and relative humidity measurements were found to be within the range of 21.36 to 26.97°C and 42.94 to 55.16%, respectively. These values have been determined to be within acceptable comfort levels, according to the literature. The CO2 concentration has been determined to increase with the number of people in the classroom and, in some cases, exceed the level of 1000 ppm, which is accepted as a general limit value, before the end of the course period. It has been determined that if the experiment is not terminated when the CO2 level rises above 1000 ppm, the CO2 level will reach even higher values depending on the elapsed time. The maximum level of CO2 was measured at 1404 ppm among the CO2 measurement data recorded before the end of the experiment. In addition, it has been determined that as the outside air intake increases, the concentration of CO2 accumulated inside decreases. This finding suggests that ventilation is necessary in fully enclosed spaces. The number of people in the class has been determined to be 35 in order to be safe in terms of CO2 levels in the activities carried out in the classroom where the research was carried out.